Buddhism and Medical Futility - Chan, Tuck; Hegney, Desley (Springer, 2012)
Religious faith and medicine combine harmoniously in Buddhist views, each in its own way helping Buddhists enjoy a more fruitful existence. Health care providers need to understand the spiritual needs of patients in order to provide better care, especially for the terminally ill. Using a recently reported case to guide the reader, this paper examines the issue of medical futility from a Buddhist perspective. Important concepts discussed include compassion, suffering, and the significance of the mind. Compassion from a health professional is essential, and if medical treatment can decrease suffering without altering the clarity of the mind, then a treatment should not be considered futile. Suffering from illness and death, moreover, is considered by Buddhists a normal part of life and is ever-changing. Sickness, old age, birth, and death are integral parts of human life. Suffering is experienced due to the lack of a harmonious state of body, speech, and mind. Buddhists do not believe that the mind is located in the brain, and, for Buddhists, there are ways suffering can be overcome through the control of one’s mind.